Предмет:
МатематикаАвтор:
анонимВынесем общий множитель за скобки:
а) 2 * a - 4 = 2 * a - 2 * 2 = 2 * (a - 2);
б) 3 * х - 2 * х^2 + x^3 = x ^ (3 - 2 * x + x^2);
в) p^2 + p * q^2 = p * (p - q^2);
г) 5 * m^2 - 10 * m * b = 5 * (m^2 - 2 * m * b) = 3 * m * (m - 2 * b);
д) 6 * x * (x - y) + y * (x - y) = (x - y) * (6 * x + y).
Автор:
soxdf0cДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть